Sinergitas Peran Pemerintah Desa dan Partisipasi Masyarakat Terhadap Perencanaan Pembangunan di Kabupaten Sidenreng Rappang: The Synergy of Village Government’s Role and Community Participation in the Process of Development Planning in Sidenreng Rappang District - Ahmad Mustanir; Fitriani S; Khaeriyah Adri; Andi Ayu Nurnawati; Goso Goso (Program Studi Ilmu Pemerintahan Fisip Universitas Mulawarman, 2020)
This research examines the role of village government, community participation, and their influences on development planning in Timoreng Panua village, Panca Rijang subdistrict, Sidenreng Rappang District. This research employed descriptive quantitative method, and involved samples of 55 households out of population of 745 households. The samples were taken randomly by using Yount formula 10%. Data was collected through observation, questionnaires and documentation, and analysed through tabulation, frequency and linear regression analysis by using SPSS 21.0 for Windows. The results show that the percentage of the role of village government contributing to the Timoreng Panua village development planning reached 52,4% (considered as ‘sufficient involvement’), while the percentage of community participation to the development planning is 77% (considered as ‘enthusiastic’). Together, the joint roles of village government and community partipation contributed to village development planning with a figure of 78,4%, categorized as ‘playing a significant role’. Keywords: community participation, government role, development planning